Experimental study of the effectiveness and exergetic efficiency of counter-rotating screw heat exchanger in a prebaked anode production plant. (5th February 2019) - Mohamed, M.A.; Tan, C.K.; Abd El-Rahman, A.A.; Wahid, S.S.; Attalla, M.; Ahmed, S.A.
Highlights: Higher mass flow rate and inlet temperature of hot stream lead to better performance. Large logarithmic mean temperature difference contributes to large exergy destruction. Between 54% and 74% of exergy of the hot stream could be potentially wasted. Measurement errors are acceptable relative to higher cost of more accurate instruments. Abstract: The current paper aims to carry out an exergy and energy analyses of the counter-rotating screw heat exchanger currently used in the prebaked anode production plant (Green Carbon Anode Plant) in Nag Hammadi Aluminum Factories. In the experiments, the flow rate of thermal oil into the coke preheater was varied from 90 m 3 /h, 100 m 3 /h, 110 m 3 /h and 120 m 3 /h and its temperature was changed from 230–260C° with step of 10 °C each test. First- and Second-law analyses were employed to evaluate the thermodynamic efficiency of the system. Studies of the impact of measurement uncertainties revealed that while the calculated effectiveness of the heat exchanger is less sensitive to that, the dimensionless exergy destruction and exergetic efficiency are more significantly affected. Further sensitivity analysis also concluded that there is not much economical value in improving the accuracy of the measurements due to the potential cost of more accurate measuring devices. Further results also showed that the effectiveness and exergetic efficiency generally improved at higher mass flow rate and inlet temperature of the hot stream. The study also found that between 54% and 74% of the available energy (i.e. exergy) of the hot stream could be potentially wasted. A large proportion of exergy destruction was due to the relatively high mean temperature difference between the hot and cold streams, which was necessary to ensure satisfactory heating of the coke by conduction. To increase the exergetic efficiency of this heating process, it is proposed that the heat losses from the heat exchanger to the environment be minimized and that the mean temperature difference (for the same rate of heat transfer) should be reduced by redesigning the heat exchanger.